Social needs realization indices in properties of forming the urban residential façade - Sanjary, Hasan Abdulrazzaq Al (Sulaimani Journal for Engineering Sciences, 2016)
Residential façade role as a social filter can be considered as a candidate one of its basic functions which express its role to achieve control of the social interaction between the resident and his surroundings and within acceptable limits that achieve the necessary privacy to him. There is no doubt that this role may like a lot of problems with the fundamental changes in the pattern of urban housing during the previous century, which has impacted on the pan-end ability to express local environmental privacy. With the availability of local studies that have dealt with this problem and presented the detailed results to solve, but it remained limited impact and the application by the problematic dealing with the priorities of the contemporary needs of the resident in the housing reality. This research tries to view and critique the previous local studies on solving this problem and discuss the constraints applied in the reality of housing, and offers by taking advantage of the facade analysis in the actual residential product, the proposed realistic indicators that can be applied to improve the social performance of the infacade in future housing projects.
Keywords: Housing facade; Resident social needs; Local architecture; City of Mosul